Investigasi Kuat Geser Antara Lapisan Permukaan Campuran Aspal Panas Akibat Pengaruh Waktu Penundaan dan Sebaran Tack Coat - Hery Awan Susanto; Kartika Fathma Dewi; Gito Sugiyanto (Rekayasa Sipil, 2023)
The hot asphalt surface layer is layered and has different functions in the pavement structure. In addition to being able to distribute the vertical load of the vehicle, it must also be able to withstand the lateral load of the vehicle. The lateral load of the vehicle that is too large causes a shear force which will have an impact on the release of the bond between the layers of hot asphalt mixture. Therefore, it is necessary to conduct research to determine the shear strength between layers of hot asphalt mixture. Several factors that cause the level of bonding strength between layers of hot asphalt mixture are the distribution of the tack coat, the setting time, the type of tack coat, and the presence of adhering dirt. The purpose of this study was to determine the effect of variations in the distribution of tack coat 0.25 and 0.35 l/m2 and setting time of 60, 90, and 120 minutes on the shear strength between layers of hot asphalt mix asphalt concrete wearing course (AC-WC) and asphalt concrete base course (AC-BC). The laboratory testing method selected by using modified soil shear test equipment. The test results show that the number of distributions and the length of setting time will cause an increase in the shear strength between the hot asphalt mixture. The maximum shear strength in the distribution of 0.25 l/m2 is 0.59 kg/cm2 and the distribution of 0.35 l/m2 is 0.64 kg/cm2 with a setting time of 120 minutes. It can also be concluded that setting time has a more significant effect on shear strength between asphalt pavement layers than the distribution of tack coat.